2017
DOI: 10.3892/ol.2017.6821
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer mechanisms of Strobilanthes crispa Blume hexane extract on liver and breast cancer cell lines

Abstract: Abstract. Cancer is a major public health concern not only in developed countries, but also in developing countries. It is one of the leading causes of mortality worldwide. However, current treatments may cause severe side effects and harm. Therefore, recent research has been focused on identifying alternative therapeutic agents extracted from plant-based sources in order to develop novel treatment options for cancer. Strobilanthes crispa Blume is a plant native to countries including Madagascar and Indonesia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 48 publications
2
7
0
1
Order By: Relevance
“…Data from the present study clearly establish the potential of ICLH extract to inhibit cell proliferation and induce apoptosis in the SCC-9 cells. These data also corroborate with similar studies performed with n-hexane extracts of other plants (Belayachi et al, 2014;Shahraki et al, 2015;Koh et al, 2017;Ng et al, 2017) including other grass species (Saleh et al, 2019). The cell cycle arrest observed at both G0/G1 and the G2/M phases of the cell cycle suggest that the active components of the extract could be acting through the G0/G1 and G2/M checkpoint machinery.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Data from the present study clearly establish the potential of ICLH extract to inhibit cell proliferation and induce apoptosis in the SCC-9 cells. These data also corroborate with similar studies performed with n-hexane extracts of other plants (Belayachi et al, 2014;Shahraki et al, 2015;Koh et al, 2017;Ng et al, 2017) including other grass species (Saleh et al, 2019). The cell cycle arrest observed at both G0/G1 and the G2/M phases of the cell cycle suggest that the active components of the extract could be acting through the G0/G1 and G2/M checkpoint machinery.…”
Section: Discussionsupporting
confidence: 90%
“…The cell cycle arrest is induced in the G0/G1 phase of the cell cycle (Saleh et al, 2019). Similar cell cycle inhibitory properties against leukemic, hepatocellular carcinoma, and breast cancer cell lines have been reported for several n-hexane extracts of various plants (Belayachi et al, 2014;Koh et al, 2017). In corroboration with these results, data from the present study showed significant induction of cell cycle arrest at both G0/G1 and G2/M phases of the cell cycle in SCC-9 cells treated with 640 μg/ml of ICLH fraction (Figure 2).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations